Malaysian contractor and their globalisation awareness / Mohamad Najib Ismail - Ismail, Mohamad Najib (2006)
Construction industry is a supporting for the manufacturing, transportation, facilities and so forth. The nation’s construction industry will require credible master plan to lead its path for future competitiveness and increasing the growth potential. Globalisation is a phenomenon that has remade the economy virtually every nation, reshaped almost every industry and touched billions of lives. Globalisation is meant to signify integration and unity. This research is carried out to understand the Malaysia construction industry and to determine the percentages of the contractor that aware about the globalisation in construction industry. This research is including the comparison level awareness between bumiputra and non- bumiputra contractors. The data collected are based on questionnaire and interview. All the data analyzed by using SPSS and Microsoft EXCEL.